CHEMICAL COMPOSITION AND BIOLOGICAL ACTIVITIES OF VOLATILE OILS OF ARABIS ALPINA L. SSP. ALPINA - O. Ucuncu (Journal of Animal and Plant Sciences, 2021)
This work reports volatile constituents, antimicrobial and antioxidant activity of volatile oils from the air-dried flower and aerial parts (APs) of Arabis alpina L. ssp. alpina. The volatile components of flower and aerial parts (stem + leaf) were investigated by means of hydrodistillation in Clevenger type apparatus and GC/MS/FID analysis. Fifty-one and fifty-three compounds in the volatile oils of flower and APs of A. alpina were identified. Terpene derivatives were the major volatiles in both oils. Hexahydrofarnesyl acetone was the main component of flower oil and APs oil in ratios of 16.27% and 26.94%, respectively. Additionally, both flower and APs essential oils were investigated for their antimicrobial activity against twelve bacteria and five fungi, using agar dilution method and antioxidant activities by using DPPH˙, ABTS˙+ and Folin-Ciocalteu assays. Flower oil was effective against B. subtilis and B. cereus even at 100µg/mL. The amount of total phenolic, %DPPH˙ scavenging activity and ABTS˙+ scavenging activity were found as 485.60±7.28 mg/mL GAE, 49.85±1.22% and 166.43±12.05µM Trolox equivalent, respectively. Flower oil exhibited antimicrobial effect against gram positive bacteria especially, and moderate antioxidant activity.
Keywords: Antimicrobial activity; Antioxidant activity; Arabis alpina L. ssp. alpina; Essential oil; GC-MS/FID; Hexahydrofarnesyl acetone